String Quartets - Lachenmann, Helmut 1935-; Stadler Quartett (Munich NEOS, 2010)
COMPOSING IN THE TONUS VIRGINEUSThe String Quartets of Helmut LachenmannI enigmatise the materialby disrobing it.Anselm KieferWhen Helmut Lachenmann was honoured for his lifes work with the Golden Lion at the 2008 Venice Biennale, the committee explained its decision by saying he had helped the material of sound to attain a new virginity. This touches on a central aspect of his creative work that has also, in many facets, found its way into his string quartets. This genre, so full of taboos, so marked by the taint of complacency in the age of student rebellions (despite important fresh approaches by composers of the stature of Boulez, Maderna and Ligeti): this genre has now found one of its most significant and original champions. New virginity means, in his case, a rejection of anything adopted without reflection. It also means opposition to anything that twists perception into misperception. But it also means repetition namely, of the great compositional discoveries that have been increasingly eclipsed and buried in the course of reception history, thereby making tradition effective as innovation. That such a back to the roots mentality can become the source of entirely new and subtle experiences, opening up the full panoply of the previously unheard, points to the dialectical basis of Lachenmanns compositional aesthetic.Perhaps this basis can be most tidily summed up in the phrase presenting by retracting. Listening to Lachenmanns string quartets, we sense how their aural landscape turns from a field of rubble into a field of tension how scrapings, draggings, scratchings and rustlings can fulfil the promise of a new beauty by avoiding the habitual. But we also sense how reflection and merriment can exist dialectically alongside and with each other. The tonus virgineus of the string quartets, for example, embodies music as an existential experience unspoilt, unaffected, disembarrassed of semantic baggage. But the same virginal inflection also seems to fulfil Lachenmanns appeal to the responsibilities of the composer, one of which is to create situations of individually altered perception and, at the same time, to provide an acoustical counterfoil to the world, drawn from the potential universe of sounds. Lachenmanns string quartets are just such situations, and in this respect they are related to that Archaic Torso of Apollo that caused Rilke, while gazing at it, to hear the call Change your life.Gran Torso marks a turning point in Lachenmanns approach to composition. It exemplifies a concept of material defined no longer by sound as an event compounded from abstract constructs, but by the mechanical and dynamic conditions of sound production itself, and on the idea of musique concrète instrumentale. Having mutated into a resonating body of sixteen strings, the quartets musicians, guided by copious explanatory notes on notation and performance, far exceed the limits of the way instruments are normally handled. The explanatory notes, worded with great fastidiousness, unparalleled imagination and a playful spirit of discovery, reveal Lachenmann to be a ne plus ultra inventor and explorer of sound. The instructions for tuning and retuning the instruments, for executing the many fingering and damping marks, for the various actions with the bow and for playing on the body, ribs and tuning pegs are worded with maximum precision, suggesting that the title Gran Torso indicates not so much an opus defectum as a work perfectly rounded in its seeming incompleteness. In this light, the performance of Gran Torso on our recording allows the listener to envision a quarry of sound from which the players hew a sort of torso with unprecedented tactile presence. This image applies equally, albeit in a different way, to the String Quartet No. 2, Reigen seliger Geister (Dance of the Blessed Spirits). This work stands out with its evanescent whisperings, its staggered, shadowy flautandi (and their timbral opposite, an effectively staged landscape of pizzicati) and the wild scordatura of its concluding section, caused by randomly twisting the tuning pegs. If the works subtitle, Reigen seliger Geister, recalls the disembodied spirit-world of Glucks Orfeo, the subtitle of the String Quartet No. 3, Grido, points to the works dramatis personae and dedicatees: the Arditti Quartet. The initials of the first names of its then members Graeme Jennings (second violin), Rohan de Saram (cello), Irvine Arditti (first violin) and Dov Scheidlin (viola) yield grido, the Italian word for scream. Here new and conventional playing techniques give rise to a new expressivity, but with no hint that Lachenmann has mellowed with age. This piece, too, has fissures, reflective fractures and a mystery the mystery that accompanies all explorations of sound and which, though allegedly a by-product, is in fact the heart and raison dêtre of music, as in every other art.Peter Becker
Keywords: 20th Century (1901-2000); String quartet